2019
DOI: 10.1038/s41419-019-1821-9
|View full text |Cite
|
Sign up to set email alerts
|

C-Jun drives melanoma progression in PTEN wild type melanoma cells

Abstract: Due to the critical impact of active AP-1 transcription factors in melanoma, it is important to define their target genes and to identify and ultimately inhibit oncogenic signals. Here we mapped the genome-wide occupancy of the AP-1 family member c-Jun in different melanoma cells and correlated AP-1 binding with transcriptome data to detect genes in melanoma regulated by c-Jun . Our analysis shows that c-Jun supports the malignant phenotype b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…Numerous studies have illuminated that the activation of CA9, STAT3, and FGF promotes the self-renewal capacity of CSCs [ 34 37 ]. Meanwhile, c-JUN, HMOX1, and CTGF play an oncogenic role in cancer [ 38 40 ]. Nevertheless, EGR1 , a member of a zinc finger transcription factor family, has been described as tumor suppressor in cancer progression [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have illuminated that the activation of CA9, STAT3, and FGF promotes the self-renewal capacity of CSCs [ 34 37 ]. Meanwhile, c-JUN, HMOX1, and CTGF play an oncogenic role in cancer [ 38 40 ]. Nevertheless, EGR1 , a member of a zinc finger transcription factor family, has been described as tumor suppressor in cancer progression [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The JNK/AP1 axis is commonly activated in benign and malignant melanoma, and promotes melanoma cell proliferation and invasion [148,[155][156][157][158]. One study showed that JNK is activated in over 75% benign nevi and it was predicted to have a role in restricting uncontrolled cell proliferation or survival.…”
Section: Jnk1 and Jnk2 In Melanoma Growth And Progressionmentioning
confidence: 99%
“…Phosphatase and tensin homolog (PTEN) was identified as a tumor suppressor and inhibited the development of multiple cancers [22][23][24]. Aside from cancers, recent studies also validated that PTEN was closely related with diabetes mellitus [25,26] and DR progression [27].…”
Section: Introductionmentioning
confidence: 99%